Assessment of skeletal age using Hand-Wrist radiographs following bjork system sample size - Prospective study - S Bhuvaneshwari; Shayon Chakravarti; Balaji Manohar; Sana Mohiuddin; L V Soujanaya Nallamilli; Dipak Chaudhari (Wolters Kluwer Medknow Publications, 2023)
Introduction: The planning of effective orthodontic therapy greatly benefits from an understanding of the skeletal maturation and stage of growth of the patients seeking orthodontic treatment. However, the patient's various craniofacial structures have varying levels of growth potential. The patient is exposed to additional radiation when hand-wrist radiographs are regularly used to forecast growth. As an alternative, cervical vertebrae in the lateral cephalograph have been suggested. When arranging orthodontic treatment for growing children, it is important to take into account the pubertal growth spurt, which is a crucial time in therapy. Conclusion: Finding out how much growth a patient with skeletal discrepancy would experience during adolescence is one of the key goals of conducting a hand and wrist radiograph.